The Reasons Behind Non-Ethical Behaviour in Business and Entrepreneurship - Fassin, Yves (Journal of business ethics, 2005)
Despite the recent increase in interest in corporate social responsibility and the propagation of corporate governance in both business and academic literature, from observations of actual practice, the author has seen at all company levels, in everyday operations, instances of non-ethical behaviour vis-à-vis the whole gamut of stakeholders. This state of affairs is linked with: pressure from stakeholders, short-term tactics, hegemony of financial considerations, ‘juridisation’ of business, the tyranny of communications and the media and the difficulties in translating strategy into practical implementation. The paper scrutinises the motivation and the psychology of entrepreneurs and business people, and their behaviour is compared to other professional groups and confronted with the decline in ethics in society as described by some important observers. The conclusion drawn is that the recent positive evolutions do not provide sufficient ethical guidelines for the day-to-day activities of middle managers and entrepreneurs in the present competitive environment. Managers will always be confronted by difficult choices with ethical dilemmas. There will always be a tension between theory and pragmatism, but progress can be made with the effective implementation of the ethical discourse in companies. To achieve this, ethical management should not be confined to the large strategic issues but also applied to the small practical matters of everyday business life. Ethics in business and entrepreneurship requires more than corporate governance and corporate social responsibility (CSR).